Gender Differences in Attitude of University Students towards Gender Roles - Nath, Meghali; Sharma, Preeti; Mittal Gupta, Ritu (Indian Journal of Extension Education, 2023)
Gender role attitude has gained considerable attention over the past three decades as the concern of society shifts from male dominance to the liberation of the female sex. This attitude of a country’s population helps in explaining deep-rooted gender sensitivity in its society. The present research was carried out purposively in Punjab Agricultural University, Ludhiana, Punjab, India in the year 2021-22 on 200 purposively selected students throwing light on the gender role attitude of University students. Primary data was collected using a structured pre-tested questionnaire. Findings revealed that half of the respondents had an egalitarian gender role attitude followed by 40.50 percent who had a transitional attitude. The majority of the female students had an egalitarian attitude whereas half of the male respondents had a transitional attitude. This gap in gender role attitude can be expected because of the male-dominated and patriarchal nature of Indian society. It is suggested that parents should be sensitized to teach their sons to share responsibilities irrespective of gender role norms and also more emphasis should be laid on gender empowerment.